Variability of functional knee phenotypes in osteoarthritic knees shows that a more personalized approach in TKA is needed. Issue 5 (28th May 2020) - Moser, Lukas; Hess, Silvan; Behrend, Henrik; Hirschmann, Michael
Aims and Objectives: Recently, the functional knee phenotype concept was introduced as a new system to classify the coronal alignment of the lower limb. Until now, this concept has only been applied to non-osteoarthritic knees. The purpose of this study was therefore to phenotype osteoarthritic knees according to this concept and investigate the distribution of these phenotypes. Materials and Methods: Preoperative CT scans of osteoarthritic knees scheduled for TKA collected between January 2017 and December 2019 in the KneePLAN 3D database (Symbios Orthopédie S.A.) were reviewed for patients meeting the following inclusion criteria: age>50 and <90, no signs of previous fractures, osteotomies and rheumatoid arthritis. A total of 2764 patients (1438 right and 1326 left lower limbs, Male:female ratio 1096 :1668) with a mean age ± standard deviation of 70±8.5years (range 50-90 years) were included. The following coronal alignment parameters were measured using a validated software (KneePLAN 3D, Symbios Orthopédie S.A): hip-knee-ankle angle (HKA), femoral mechanical angle (FMA), and tibial mechanical angle (TMA). Based on these measurements each leg was phenotyped according to the functional knee phenotype concept and the distribution of these phenotypes assessed. A phenotype thereby consists of a phenotype specific mean value (HKA, FMA or TMA value) and covers a range of ± 1.5° from this mean (e.g. 180°± 1.5). The phenotype specific mean values represent 3° increments of the angle starting from the rounded overall mean value of the angle. Results: There were 162 different functional knee phenotypes (122 male, 138 female and 97 mutual). The most common functional knee phenotype in males was VARHKA6°VARFMA3°NEUTMA0° accounting for 8% of all males. The most common functional knee phenotype in females was VARHKA3°NEUFMA0°NEUTMA0° accounting for 9% of the population. The ten most common functional phenotypes account for 50% and 42.8% of all females and males, respectively. Overall, 134 phenotypes accounted each for less than 1% of the total population (all 134 together for 26.4%). Conclusion: The broad variability of functional knee phenotypes in osteoarthritic knees shows that a more personalized TKA realignment strategy is needed. The challenge will be to identify the optimal alignment strategy for each functional knee phenotype.